Physiochemical and microbiological quality assessment and detection of adulterants of raw milk available in Nakla Upazila, Sherpur, Bangladesh (SAARC Journal of Agriculture, 2017)
Abstract not availableSAARC J. Agri., 14(2): 210-217 (2016)